PROLONGED GESTATION IN A SHEEP ASSOCIATED WITH A CYCLOPIC - KUMAR, ANIL; R, VENKATARAMANAN; M, IYUE (The Indian Journal of Animal Reproduction, 2023)
A case of prolonged gestation associated with Cyclops in sheep was reported.
Keywords: Cyclopia; prolonged gestation; sheep